Urethrotomy of the glans penis in three male dogs with urolithiasis. (22nd July 2015) - Cinti, F.; Pisani, G.; Carusi, U.; Buracco, P.
Abstract : Three intact male dogs with stranguria and haematuria caused by uroliths in the penile urethra underwent urethrotomy using a novel surgical approach directly over the caudal part of the os penis because conservative procedures to resolve the obstructions had failed. Haemorrhage was minimal, and the incisions healed rapidly by second intention. Complications did not occur during the 6‐month follow‐up period. Urethrotomy directly over the os penis is straightforward, associated with few complications and holds promise for the removal of urinary calculi in the penile urethra.